SAFE 2025 National Sustainability Assessment - Kouikoglou, Vassilis; Phillis, Yannis (IEEE International Conference on System of Systems Engineering (Online), 2025)
Sustainability Assessment by Fuzzy Evaluation (SAFE) is a model widely used to measure sustainability in the context of nations, cities, corporations and other entities. Its 2025 version presented here provides sustainability scores and rankings for 161 countries. SAFE uses time series for 68 basic indicators regarding environmental and socioeconomic national performance. Each time series is converted to a single sustainability score between 0 and 1 via appropriate smoothing, imputation and normalization algorithms to remove measurement noise and fill in missing values. A multistage rulebased fuzzy inference procedure aggregates the normalized indicators into composite variables which yield an ecological and human component per country. These two components are finally aggregated into an overall sustainability index. Next a sensitivity analysis uncovers the most important indicators that affect sustainability. Most countries have made modest progress towards sustainability over 2000-2024. Developed countries exhibit contradictory performance. Several of them occupy the top places of the ranking but others show a decline in both the ecological and human components.